2013
DOI: 10.2147/ppa.s45777
|View full text |Cite
|
Sign up to set email alerts
|

Patient health information materials in waiting rooms of family physicians: do patients care?

Abstract: BackgroundPatient health information materials (PHIMs), such as leaflets and posters are widely used by family physicians to reinforce or illustrate information, and to remind people of information received previously. This facilitates improved health-related knowledge and self-management by patients.ObjectiveThis study assesses the use of PHIMs by patient. It also addresses their perception of the quality and the impact of PHIMs on the interaction with their physician, along with changes in health-related kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…A study showed that patient information leaflets are appreciated by patients because these have the potential to enhance patient–physician interaction, health-related knowledge and self-management. 25 This makes patient information leaflets attractive in general. However, these might not be suitable for every indications, since there are also studies that show that leaflets, for example, about medication side effects, are not used by many patients and have a negative effect in the patients that do use them by increasing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that patient information leaflets are appreciated by patients because these have the potential to enhance patient–physician interaction, health-related knowledge and self-management. 25 This makes patient information leaflets attractive in general. However, these might not be suitable for every indications, since there are also studies that show that leaflets, for example, about medication side effects, are not used by many patients and have a negative effect in the patients that do use them by increasing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Printed educational materials are commonly offered in waiting rooms, but their efficacy has been shown in studies to be highly variable, and dependent upon the specific contexts, populations, and formats involved [10,13,21]. Beyond printed materials, there has been a lack of innovative approaches to education in the waiting room that both robustly utilize available technologies and also attempt to reach underserved groups [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from a variety of Western healthcare settings report that using audio-visual health promotion messages can better teach patients about their condition, increase confidence in self-management, and promote active communication and shared decision making with physicians [ 3 , 11 ]. Specifically to General Practice settings, studies from French [ 12 ] and Belgian [ 13 ] general practitioners have suggested that clinical waiting rooms are an acceptable and useful medium for health promotion; the former study placing particular importance on the effects of television health promotion [ 12 ]. Another Belgian study showed that broadcasting audio-visual health information about vaccinations was significantly associated with increased adult tetanus booster prescriptions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%